The Role of Artificial Intelligence in Optimizing Human Resource Management in Islamic Educational Institutions - Duwi Habsari Mutamimah; Binti Maunah (International Journal of Science and Applied Science: Conference Series, 2024)
Islamic educational institutions encounter significant challenges in human resource management due to the rapid advancement of digital technology. To enhance quality and efficiency, these institutions must embrace innovative solutions, particularly the integration of artificial intelligence (AI) within the context of the Industrial Revolution 4.0. This research aims to explore the potential applications of AI in human resource management (HR) specifically within Islamic educational settings, while also identifying the opportunities and challenges associated with its implementation. Utilizing a qualitative approach through a comprehensive literature review, this study collects data from secondary sources to identify key themes and gaps in existing literature, ultimately formulating recommendations for effective AI integration. The findings reveal that AI can significantly improve operational efficiency, facilitate data-driven decision-making, and enhance the professional development of staff in Islamic educational institutions. However, challenges such as resistance to change and limited resources must be addressed. The strategic implementation of AI can foster an environment conducive to the professional growth of educators, aligned with Islamic values. This research not only provides valuable insights into the role of technology in HR management but also emphasizes the necessity for further studies to explore additional dimensions of AI application in educational contexts. Ultimately, this study enriches the understanding of AI's role in HR management within Islamic educational institutions and serves as a reference for administrators seeking to adopt advanced technological solutions.